Deiksis in the Novel Dunia Anna by Jostein Gaarder - Erwin, Muh; Lanta, Jumiati; Hanafi, Muhammad; Hermansyah, Sam; Suleha, Suleha (Journal International of Lingua and Technology, 2024)
This article aims to describe the forms of deixis and their reference meanings found in the novel Dunia Anna by Jostein Gaarder. This article is a study that uses a qualitative descriptive method. The data are in the form of words, phrases, sentences that contain deixis in the novel Dunia Anna. The data collection techniques in this study were intensive reading techniques and recording techniques, after which the data were analyzed using the Yule theory with the Miles and Huberman models, namely data reduction, data presentation, and conclusions/verification. Based on data analysis, five forms of deixis were found in the novel Dunia Anna by Jostein Gaarder, namely persona deixis, place deixis, time deixis, discourse deixis, and social deixis. The forms of personal deixis found include 1) (I) and (I) as the first singular personal deixis, 2) (we) and (us) as the plural first person deixis, 3) (you), (you) and (you) as second person singular deixis, 4) (you) as plural second person deixis, 5) (he) and (she) as third person singular deixis, 6) (they) as third person plural deixis. Whereas the forms of place deixis are here, there, and there. While the deixis of time are, present time, past time and future time. Discourse deixis and social deixis are also found in this novel. Discourse deixis includes anaphora and cataphora while social deixis includes age, gender, occupation, and social position. The conclusion of this article is the use of the form of persona deixis that dominates the forms of deixis found in the novel, this is because the characters in the story often mention themselves in the dialogue.